Measuring Benefits of Hajj Zam-Zam Savings Bank Panin Dubai Syariah Bandung Through Product Quality and Service - Sugiarto Halim; Yuda Dharma Putra (Universitas Bina Sarana Informatika, 2025)
Reviewing the potential of the graph shows that the number of Indonesian pilgrims registering and departing for Umrah and Hajj each year continues to increase, which provides a great opportunity for Islamic travel and financial service providers. Meanwhile, one of the services that offer Hajj and Umrah Savings products is Islamic Banking, which strives to educate users, promote services, and improve their quality. Based on problem identification, it can be stated that information regarding Hajj savings in Islamic banking is still unevenly distributed to the wider community, as well as the limitations and availability of Islamic banks which are still unevenly distributed in various cities. The data collection techniques used are interviews and distributing questionnaires to users. This research method uses quantitative methods to examine the development of theories that they have developed based on the knowledge and insights they have regarding the Quality of Zam-Zam Hajj Savings Products at PT Bank Panin Dubai Syariah Tbk KC Bandung. This research is expected to be useful for parties who intend to save their money in Islamic banks and provide information to Islamic bank managers about how to channel customer funds properly and correctly in accordance with community regulations. and can be used as a guideline as well as additional information for the benefit of future research development.